Advertising and attachment: exploiting loss aversion through prepurchase information. (13th November 2017) - Karle, Heiko; Schumacher, Heiner
Abstract: We analyze a monopolist's optimal advertising strategy when consumers are expectation‐based loss‐averse and uncertain about their individual match value with the product. Advertising provides verifiable match value information. It modifies the consumers' reference point and hence their willingness to pay for the product. We show that the optimal advertising strategy pools different consumer types so that some consumers engage in ex ante unfavorable trade. Incomplete informative advertising thus has a persuasive effect. This provides a rationale for policies that force the monopolist to disclose important product characteristics, not only at the point of sale, but also in all promotional materials.